2018
DOI: 10.1371/journal.pone.0202884
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and dynamic characterization of prosthetic feet for high activity users during weighted and unweighted walking

Abstract: Many Service members and Veterans with lower-limb amputations have the potential for high function and the desire to resume physically demanding occupations that require them to carry heavy loads (e.g., military service, firefighters, farmers, ranchers, construction workers). However, it is currently unclear which prosthetic feet best accommodate heavy load carriage while also providing good overall function and mobility during unweighted activities. The main objective of this study was to investigate the abil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 22 publications
(35 reference statements)
0
15
0
Order By: Relevance
“…In addition to stiffness quantification, methods of mechanically testing prosthetic feet vary across studies. Although there have been numerous previous studies that have mechanically tested prosthetic feet, we identified three such studies that were similar to the current study in the types of prosthetic feet (size, stiffness category, and model (i.e., Rush HiPro,[ 18 ] AllPro,[ 18 ] Vari-Flex,[ 16 ] and Seattle Lightfoot2[ 16 , 17 ])) and pylon progression angles tested. In the current study we used an R2000 Rotopod for mechanical testing.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…In addition to stiffness quantification, methods of mechanically testing prosthetic feet vary across studies. Although there have been numerous previous studies that have mechanically tested prosthetic feet, we identified three such studies that were similar to the current study in the types of prosthetic feet (size, stiffness category, and model (i.e., Rush HiPro,[ 18 ] AllPro,[ 18 ] Vari-Flex,[ 16 ] and Seattle Lightfoot2[ 16 , 17 ])) and pylon progression angles tested. In the current study we used an R2000 Rotopod for mechanical testing.…”
Section: Discussionmentioning
confidence: 85%
“…Several studies also have used a “functional” or instantaneous stiffness estimate, in which linear regression was fit to a smaller region of the force-displacement curve, at a particular load level (e.g., approximating near body weight). [ 6 , 16 , 18 ] However, distilling the information from each force-displacement curve to a single value of stiffness may be better suited for a foot with linear behavior, and is likely less representative of many contemporary prosthetic feet. Since many prosthetic feet have curvilinear behavior, one study described using a 2 nd order polynomial, in addition to calculating the linear stiffness of feet across the full curve, as it provided a better representation of the nonlinear force-displacement curve.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,6 To measure linear stiffness in a user-independent manner, investigators have used mechanical testing procedures. [7][8][9][10][11] Tests for linear stiffness typically generate force-displacement data curves from quasi-static loading conditions in which the prosthetic foot is positioned at a fixed angle relative to the loading platform. Previous mechanical testing methods have reduced tangential shear forces to avoid overconstraining the system during loading, often incorporating a roller plate (RoPl) with ball bearings into the loading platform.…”
Section: Introductionmentioning
confidence: 99%
“…3,6 To measure linear stiffness in a user-independent manner, investigators have used mechanical testing procedures. 7-11…”
Section: Introductionmentioning
confidence: 99%